The Role Of Digital Health Technology In Enhancing Health Promotion Campaigns : A Case Study From A Resource Imites Region - Rita Rena Pudyastuti; Johanna Tomasoa; Andrias Horhoruw; Marta Atik Martsiningsih (Oshada, 2024)
Study This evaluate role technology digital health in increase effectiveness campaign promotion health in the region with source Power limited use method studies literature . Focus main is understand contribution application health , social media platforms , and services message short (SMS) in expand reach and impact information health , as well as identify challenges and solutions related its application . This method involving review systematic to relevant literature , including​ article journal , report research , and publication about technology digital health . Analysis aiming collect data about effectiveness technology , challenges faced, and strategies implemented . Findings show that technology digital health has the potential big in repair access information health , improve awareness society , and encourage behavior healthy. Limitations internet access and low digital literacy can hinder utilization technology. The proposed solution covering investment in infrastructure technology information , improvement digital literacy through training , and work The same between government , sector private sector , and non- governmental organizations . Technology digital health can become tool effective in reach objective health a more society good and even , especially in areas with source Power limited , with support and planned strategies. Research This give outlook about optimization technology digital health based proof studies literature For results better health​ Good .